2022
DOI: 10.1007/s11191-022-00325-3
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Pre-service Science Teachers’ Understanding of Scientific Inquiry and Scientific Practices Through a Laboratory Course

Abstract: The intervention study presented in this paper explored pre-service science teachers' (PSSTs) understanding of scientific inquiry (SI) and scientific practices (SPs) during a laboratory application in science education course. Thirty-nine secondary school PSSTs, who study in the Science Education Department in a public university in Turkey, enrolled in a 14-week-long course and volunteered to participate in the study. The participants were exposed to a method is called the 4-phase implementation that includes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
2
0
5

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 56 publications
1
2
0
5
Order By: Relevance
“…This had the impact of hindering their ability to plan and design investigations in under-resourced rural environments, where most of them are often deployed after completing their studies. The study findings indicate inadequate knowledge of variables and issues of validity and reliability and concur with the findings of Ozer and Sarıbaş [37], which indicated that preservice teachers had an inadequate understanding of inquiry in some aspects, even after the treatment.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…This had the impact of hindering their ability to plan and design investigations in under-resourced rural environments, where most of them are often deployed after completing their studies. The study findings indicate inadequate knowledge of variables and issues of validity and reliability and concur with the findings of Ozer and Sarıbaş [37], which indicated that preservice teachers had an inadequate understanding of inquiry in some aspects, even after the treatment.…”
Section: Discussionsupporting
confidence: 87%
“…Additionally, this study's findings are in line with the findings in Yustina et al's [24], and Valls-Bautista et al's [35] studies, which indicate that intervention strategies improve students' inquiry-based skills. However, Ozer and Sarıbaş [37] indicate that intervention strategies only improve some of the students' inquiry-based skills, especially if the intervention is administered over a short period of time. For greater skill development, several interventions need to be implemented.…”
Section: Discussionmentioning
confidence: 99%
“…There is a general consensus that PSETs need opportunities to plan and conduct high‐quality investigations to support science instruction in future K‐12 classrooms (National Research Council, 2012; Özer & Sarıbaş, 2023). To date, much research has cast a deficit perspective on PSETs' ability to plan and carry out investigations (Crawford, 2007; Gray et al, 2022).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Studies have shown that it is possible to ensure this development with comprehensive training that is continuous, and enriched with practical experiences (Capps and Crawford, 2013b;Loucks-Horsley et al, 2003;Özer and Sarıbaş, 2023;Plevyak, 2007;Windschitl, 2003). However, it was observed that these studies were mostly aimed at secondary and high school science teachers and preservice teachers (Capps and Crawford, 2013b;Loucks-Horsley et al, 2003;Özer and Sarıbaş, 2023;Windschitl, 2003). However, there are limited studies on preschool teachers or preservice teachers (Plevyak, 2007).…”
Section: Extended Abstractmentioning
confidence: 99%